Escola Municipal de Educação Infantil Paraíso da Criança em Agudo/RS: processos de documentação pedagógica na creche - Unfer, Emanueli (2022)
The present paper researched which experiences allow us to observe democratic processes which enhance pedagogical practices on childhood school from documentation produced in the last 5 years on Child Education Day Care, with the goal of thinking about the actions of day care, allowing a reflection about democracy in pedagogical cause, as well as the participation of the children in a respectful manner. This research is linked to the professional masters degree of the Universidade Federal de Santa Maria (UFSM), in the second line of research - Pedagogical Management and Educational Contexts. The option for this theme is justified by the experiences of the author as a teacher in Child Educations and subsequently as Secretária Municipal de Educação e Desporto. The goal of this research is to study the pedagogical documentation gathered on the last 5 years on and for the Day Care/Child Education of Agudo/RS, looking to stabilish ties of the democratic processes as enhancers of pedagogical practices in childhood school. This research travels through many roads, paths and crossings as a metaphor for the buildings of cities in building blocks that the author does with her daughter. For us to get those results, we have utilized as main references Morin, Dahlberg, Moss, Pence, Pikler, Freire, Junqueira Filho, Gandini, Ostetto, Rinaldi and many legal documents that regulate Child Education in Brazil. The research is being developed with a qualitative approach, of applied and implicit nature, always considering the scholar context. The research was done in documents of the School’s archives. The main body of the research is an online receptacle of pedagogical documentations produced on the school, with the goal of providing future research, as well as the attendance of the educational teachers of the children that attend or attended the school.